Calculation of deflection of one- and two-layer slabs supported on four sides - Smorkalov, D. (KNUCA, 2014)
Presented method and results of experimental research of deflection of one-layer and two-layer slabs influenced by short-term lateral load. Proposed method of calculation based on the limit equilibrium method, calculation of slab deflections values by LIRA-CAD bundled software. The comparison of experimental and theoretical results of the calculation of deflections slabs.
Расчет прогибов одно- и двухслойных плит, опертых по контуру
Keywords: slab; deflection; steel fiber concrete; плита; прогиб; сталефибробетон